Differentially Expressed Proteins Associated with Fusarium Head Blight Resistance in Wheat - Zhang, Xianghui; Fu, Jianming; Hiromasa, Yasuaki; Pan, Hongyu; Bai, Guihua; Yan, Wengui (PloS one, 2013)
Fusarium head blight (FHB), mainly caused by Fusarium graminearum , substantially reduces wheat grain yield and quality worldwide. Proteins play important roles in defense against the fungal infection. This study characterized differentially expressed proteins between near-isogenic lines (NILs) contrasting in alleles of Fhb1 , a major FHB resistance gene in wheat, to identify proteins underlining FHB resistance of Fhb1 . The two-dimensional protein profiles were compared between the Fusarium -inoculated spikes of the two NILs collected 72 h after inoculation. The protein profiles of mock- and Fusarium -inoculated Fhb1 + NIL were also compared to identify pathogen-responsive proteins. Eight proteins were either induced or upregulated in inoculated Fhb1 + NIL when compared with mock-inoculated Fhb1 + NIL; nine proteins were either induced or upregulated in the Fusarium -inoculated Fhb1 + NIL when compared with Fusarium -inoculated Fhb1 − NIL. Proteins that were differentially expressed in the Fhb1 + NIL, not in the Fhb1 − NIL, after Fusarium inoculation included wheat proteins for defending fungal penetration, photosynthesis, energy metabolism, and detoxification. Coordinated expression of the identified proteins resulted in FHB resistance in Fhb1 + NIL. The results provide insight into the pathway of Fhb1 -mediated FHB resistance.